ANALISIS KESALAHAN BERBAHASA DALAM BIOGRAFI PRAMOEDYA ANANTA TOER KARYA MUHAMMAD RIFAI - Bekti Oki Mulyani Putri; Rinawati Rinawati; Maghfiroh Kurniawati (Universitas Sarjanawiyata Tamansiswa, 2020)
Language error analysis is a method used in language learning, which aims to find out language mistakes made by students. This study aims to determine the language errors contained in the biography of Pramoedya Ananta Toer written by Muhammad Rifai. Using qualitative methods by reading and examining Pramoedya Ananta Toer's biography to find out the errors contained in the biography, the technique used for data collection is literature review by carefully reading Pramoedya Ananta Toer's biography to find out what errors are found in the biography. While the data analysis technique is to classify the errors found and then analyzed in accordance with these errors. From the biography there are errors in (1) phonology (there are 1 errors in phoneme change and there are 2 errors in phoneme removal), (2) morphology (sound errors that should be melted, but there are no errors and 1 error is used), (3) syntax (phrase field errors there are 2 errors, redundant word errors there are 2 errors and errors in the sentence field there are 6 errors), preposition errors there are 1 errors), (4) semantics (errors in the choice of words there are 4 errors), and language errors in the application of spelling (punctuation errors there are 2 errors. So the number of errors found is 22 errors.